EXAMINING HOW WHEELCHAIR BASKETBALL PLAYERS’ SELF-ESTEEM AND MOTIVATION LEVELS IMPACT ON THEIR STATE AND TRAIT ANXIETY LEVELS - Hakan Kolayis (Biology of Sport, 2012)
The purpose of the study was to examine how wheelchair basketball players’ self-esteem and motivation levels impact on their state and trait anxiety levels. The Coopersmith Self-Esteem Inventory, Sport Motivation Scale and STAI (State Trait Anxiety Inventory) were applied to the athletes before a competition. Data were collected from 124 athletes with disabilities. In this study, descriptive statistical techniques, Pearson product moment correlation and multiple regression analysis (enter method) were used. Multiple regression analyses indicated that self-esteem, intrinsic motivation, extrinsic motivation and amotivation, all of which function as predicting variables, predicted 42% variance in state anxiety and 50% variance in trait anxiety. Motivation and self-esteem are the best predictors of trait and state anxiety among the premier league wheelchair basketball players. Finally, a review of factors that impact on anxiety and quality of performance such as motivation and self-esteem is provided.